# Solve the system by elimination?

{3a+4b=9

{-3a-2b=-3

### 12 Answers

- PinkgreenLv 73 weeks ago
3a+4b=9------(1)

-3a-2b=-3-----(2)

(1)+(2)=>

2b=6=>

b=3

(1)+2*(2)=>

-3a=3=>

a=-1

The answer is

a=-1

b=3

- formengLv 63 weeks ago
First add the two equations to eliminate the variable "a."

3a + 4b = 9

-3a-2b =-3

----------------

2b = 6

b=3

Now, substitute the value of "b' into either equation.

3a + 4(3) = 9

3a = 9-12 (Subtract 4(3) = 12 from both sides of the equation.)

3a = -3

a= -1

Answer (a, b) = ( -1, 3)

- lenpol7Lv 73 weeks ago
Subtract the two equations. This will eliminate 'a'

Hence

2b = 6

b = 3

When b = 3

3a + 4(3) = 9

3a + 12 = 9

3a = -3

a = -1

- PhilipLv 63 weeks ago
3a+4b = 9...(1).;

-3a-2b = -3...(2).;

(1)--->3a=9-4b;

Substitute (9-4b) for the 3a in (2) getting -(9-4b)-2b = -3;

ie., 9-4b+2b=3;

ie., 9-2b=3;

ie., 2b=9-3 = 6;

ie., b = 3;

Then (1)---> 3a = 9-12 = -3;

ie., a = -1.;

- How do you think about the answers? You can sign in to vote the answer.
- la consoleLv 73 weeks ago
(1) : 3a + 4b = 9

(2) : - 3a - 2b = - 3

You calculate (1) + (2)

(3a + 4b) + (- 3a - 2b) = 9 + (- 3)

3a + 4b - 3a - 2b = 9 - 3

2b = 6

→ b = 3

Recall (1) : 3a + 4b = 9

3a = 9 - 4b → where: b = 3

3a = - 3

→ a = - 1

- Anonymous3 weeks ago
Surprising how many people get their education on Yahoo! Answers. Could be why the world is so screwed up nowadays.If you can't cook, get out of the kitchen.

- Engr. RonaldLv 73 weeks ago
{3a+4b=9 ... eq1

{-3a-2b=-3 .. eq2

----------------

2b = 6

b = 3 Answer//

solving for a from eq1

3a + 4b = 9

3a + 4(3) = 9

3a + 12 = 9

3a = 9 - 12

3a = - 3

a = - 1 answer//

- Jeff AaronLv 73 weeks ago
Add the equations:

2b = 6, so b = 6/2 = 3

Multiply the second equation by 2:

-6a - 4b = -6

Add that to the first equation:

-3a = 3

a = 3/(-3) = -1